Hubungan Antara Pengetahuan Terminologi Medis Petugas Rekam Medis Dengan Ketepatan Kode Diagnosis Di Rs Pku Muhammadiyah Yogyakarta - SAPUTRO, NIKO; , Ibunu Mardiyoko, SKM, MM (2016)
Lack of medical terminology knowledge of medical records officer was affected on the inaccuracies diagnosis code. The purpose of this study was to determine the correlation between the medical terminology knowledge of medical records officer with the accuracy of a diagnosis code generated by medical records officer at the RS PKU Muhammadiyah Yogyakarta. This research uses observational analytic study with cross sectional study design. The population in this study are all medical records officer who works at the RS PKU Muhammadiyah Yogyakarta, amounting to 13 people. Mechanical sampling of the population used in this study is total sampling, where all of the population used as a sample. The analysis showed that the percentage of medical records officer in the group of lack medical terminology knowledge (53.8%) was higher than in group of good one (46.2%). The percentage of medical records officer that produces inaccurate diagnostic code (46.2%) was lower than produced accurate one (53.8%). The result of the correlation using fisher's exact test showed that Ho accepted where the value of p = 0.617 (p < 0.05). This shows there is no correlation between the medical terminology knowledge of medical records officer with the accuracy of diagnoses code were generated by medical records officer at the RS PKU Muhammadiyah Yogyakarta.